A Case Study on Solar Vapour Absorption Refrigeration System - Girish K.V.S., Shabari; R, Praveen; Nair, Dipesh; Sahu, Debjyoti (International Journal of Engineering and Technology, 2018)
Solar refrigeration may have applications in both developed and developing countries. Applications in developing countries such as air-conditioning, vaccine storage or large scale food preservation have been the subject of scientific research. Ammonia-water based system has good COP but generally vapor absorption refrigeration system requires high generator temperature and high circulating ratio aided by a powerful pump. Our objective was to trivialize the role of circulating ratio and simultaneously achieve higher COP. A prototype model was designed, fabricated in laboratory using scrap material and tested; performance of the unit has been analyzed. A parabolic solar trough was used as a source of heat. Various components were modeled in computer and analyzed using ANSYS. The performances and effectiveness of the unit was studied by determining refrigeration effect (RE) and   coefficient of performance (COP).